Fiduciary Duty of Loyalty and Corporate Culture - Hu, Maggie Rong; Jiang, Cheng; John, Kose; Ju, Ming (The Review of Corporate Finance Studies, 2026)
Abstract We investigate the impact of the fiduciary duty of loyalty on corporate culture. Leveraging the staggered state adoption of corporate opportunity waiver (COW) laws as an exogenous fiduciary loyalty decline, we find that COW laws deteriorate corporate culture. This effect operates through increased board overlapping and director busyness and is more pronounced in firms with legal-expert directors, weaker governance, and greater outside opportunities as well as in smaller or younger firms. The results are robust across alternative measures, time frames, legislative events, estimation strategies, etc. Overall, the fiduciary duty of loyalty plays a crucial role in enhancing corporate culture and firm performance. (JEL G34, G38, M14)